2007
DOI: 10.1073/pnas.0609410104
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dysfunction as a cause of genomic instability in Werner syndrome

Abstract: Werner syndrome (WS) is a rare human premature aging disease caused by mutations in the gene encoding the RecQ helicase WRN. In addition to the aging features, this disorder is marked by genomic instability, associated with an elevated incidence of cancer. Several lines of evidence suggest that telomere dysfunction is associated with the aging phenotype of the syndrome; however, the origin of the genomic instability observed in WS cells and the reason for the high incidence of cancer in WS have not been establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(174 citation statements)
references
References 33 publications
7
167
0
Order By: Relevance
“…Covalent fusion of the chromosomal ends may induce genomic instability due to the random DNA break during anaphase [50]. It has recently been proposed that replication-associated telomere loss and resultant chromosome fusions may be the cause of genomic instability seen in the classical Werner syndrome caused by WRN helicase gene mutations [51]. It is conceivable that the increased apoptosis [19] and DNA accumulation [52] seen in HGPS may be, at least in part, secondary to accelerated telomere loss.…”
Section: Discussionmentioning
confidence: 99%
“…Covalent fusion of the chromosomal ends may induce genomic instability due to the random DNA break during anaphase [50]. It has recently been proposed that replication-associated telomere loss and resultant chromosome fusions may be the cause of genomic instability seen in the classical Werner syndrome caused by WRN helicase gene mutations [51]. It is conceivable that the increased apoptosis [19] and DNA accumulation [52] seen in HGPS may be, at least in part, secondary to accelerated telomere loss.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the mouse Mgs1 orthologue, Wrnip1 (Werner-interacting protein 1) was cloned as a binder of the helicase (Wrn) mutated in the Werner syndrome (4,5). Telomere aberrations and defective telomere laggingstrand replication have been proposed to be a key patho-mechanism of this very rare premature aging condition, which remarkably recapitulates the main features of physiological aging (6,7). In S. cerevisiae, mgs1 was found to be synthetically lethal with the rad6 and rad18 genes involved in DNA damage tolerance, indicating that Mgs1/Wrnip1 might deal with stalled replication forks (8).…”
mentioning
confidence: 99%
“…Although prior experiments have shown that suppression of the pRb and p53 DNA damage checkpoint pathways by viral oncoproteins enables bypass of replicative senescence in WS cells (16)(17)(18), to our knowledge there have not been any experimental investigations of the neoplastic conversion of WS cells or the properties of cancer cells from WS patients. In previous studies we showed that normal human fibroblasts require only the combination of oncogenic Ras and SV40 large T antigen (SV40 LT) to be converted to fully tumorigenic cells, as evidenced by their ability to form invasive and metastatic tumors in the subrenal capsule assay in immunodeficient mice (19,20).…”
Section: Introductionmentioning
confidence: 96%